2021
DOI: 10.1186/s40794-021-00149-z
|View full text |Cite
|
Sign up to set email alerts
|

Death as attraction: the role of travel medicine and psychological travel health care in ‘dark tourism’

Abstract: Still an evolving field in travel medicine, psychological travel health has not yet been linked to tourist products that may affect travellers’ mental wellbeing. Dark tourism, the travel to sites linked to death, atrocities and suffering, is a product that, on the one hand, attracts people with a keen interest in death-related attractions and, on the other hand, may inflict psychological scars. Of particular concern are travellers with undiagnosed or diagnosed mental illness.This is the first article bringing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Abraham et al [ 58 ] studied the emotions of the victims' descendants in visiting dark tourism sites and found that the image of these sites was a mediator between emotions of animosity and grief. Bauer [ 59 ] studied the impact of death as an attraction of travelers whose scars remain invisible, especially on those with a diagnosed mental illness. Moreover, Prayag et al [ 77 ] apprised mortality salience and significance in life for locals visiting dark tourism sites.…”
Section: Discussionmentioning
confidence: 99%
“…Abraham et al [ 58 ] studied the emotions of the victims' descendants in visiting dark tourism sites and found that the image of these sites was a mediator between emotions of animosity and grief. Bauer [ 59 ] studied the impact of death as an attraction of travelers whose scars remain invisible, especially on those with a diagnosed mental illness. Moreover, Prayag et al [ 77 ] apprised mortality salience and significance in life for locals visiting dark tourism sites.…”
Section: Discussionmentioning
confidence: 99%
“…Travelers’ syndromes include Stendhal syndrome and Jerusalem syndrome, which manifest as psychological symptoms, perceptual disorders, persecutory feelings, states of anxiety, depressive feelings, or euphoria. Sometimes, there may be an omnipotent thought and an absence of self-criticism where the patient usually feels disoriented and confused ( Beyle, 1999 ; Bauer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The second type generates anguish; feelings of inferiority, precariousness, or insufficiency; superiority; euphoria; and exaltation, in addition to a loss of the criterion of reality ( Beyle, 1999 ). Finally, the third type is related to panic or fainting attacks, tachycardia, epigastric discomfort, and chest pain ( Bauer, 2021 ). For the three syndromic types, repressed sexual drives, fatigue, insufficient sleep, the end of a trip, and vital moments of uncertainty or change are identified as potentially triggering factors ( Bauer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation